2019
DOI: 10.1186/s12879-019-3978-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Mycobacterium tuberculosis sensitivity to rifampicin and isoniazid in South Gondar Zone, northwest Ethiopia

Abstract: Background Drug resistant tuberculosis (TB) has become a persistent health threat in Ethiopia. In this respect, baseline data are scarce in many parts of high TB burden regions including the different zones of Ethiopia. Methods A total of 111 culture positive M. tuberculosis isolates were recovered from TB patients and identified using region of difference (RD) 9 based polymerase chain reaction (PCR) and spoligotyping. Thereafter, their drug s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
48
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(76 citation statements)
references
References 32 publications
20
48
8
Order By: Relevance
“…From the tested isolates 93.2% were fully susceptible to both INH and RIF, and 6.8% of the isolates were resistant to at least one of the tested anti-TB drugs. This is relatively lower than previous reports from different parts of the country [ 8 , 9 ]. In a similar manner lower level of INH and RIF resistance was reported from drug naïve TB patients in East Africa [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…From the tested isolates 93.2% were fully susceptible to both INH and RIF, and 6.8% of the isolates were resistant to at least one of the tested anti-TB drugs. This is relatively lower than previous reports from different parts of the country [ 8 , 9 ]. In a similar manner lower level of INH and RIF resistance was reported from drug naïve TB patients in East Africa [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 60%
“…Likewise, a study conducted by Alelign et al reported the existence of a high proportion of drug-resistant M . tuberculosis strains from South Gondar Zone, northwest Ethiopia [ 9 ]. All these studies emphasized the significance of the drug resistance-conferring gene mutations in M .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that more than 95% of rifampin resistance is because of point mutations in the rpoB gene (the RNA polymerase beta subunit encoding gene). [ 4 ] The most frequent mutations related to rifampin resistance in mycobacterium tuberculosis are replacements at codons 531, 526, and 516 in the rpoB gene, respectively. Mutations in these three codons are the factor for 70 to 95% of resistance to rifampin.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in these three codons are the factor for 70 to 95% of resistance to rifampin. [ 4 ] Isoniazid is another effective drug in TB treatment. Isoniazid resistance happens due to mutations in several genes, the most important of which are inhA and katG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation